1995
DOI: 10.1046/j.1471-4159.1995.64062773.x
|View full text |Cite
|
Sign up to set email alerts
|

Glial‐Neuronal Interactions as Studied by Cerebral Metabolism of [2‐13C]Acetate and [1‐13C]Glucose: An Ex Vivo 13C NMR Spectroscopic Study

Abstract: Mice were injected intravenously with [2‐13C]‐acetate or [1‐13C]glucose and killed after 5, 15, or 30 min. Another group of animals was injected three times subcutaneously during 30 min with [2‐13C]acetate to achieve a steady‐state‐like situation. Brain extracts were analyzed by 13C NMR spectroscopy, and the percent enrichment of various carbon positions was calculated for amino acids, lactate, and glucose. Results obtained with [2‐13C]acetate, which is metabolized by glia and not by neurons, showed that gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
126
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 153 publications
(153 citation statements)
references
References 17 publications
22
126
5
Order By: Relevance
“…As expected from previous studies of the metabolism of 1-14 C-acetate (Berl and Frigyesi, 1969;Haberg et al, 2001;Hassel et al, 1995), 14 C-radiolabel was also incorporated into glutamate, but at a lower specific activity than glutamine. The initial production of 14 C-glutamate from 14 C-acetate is also predominantly astrocytic based on the substantial impairment produced by the selective glial aconitase inhibitor, fluorocitrate (Fonnum et al, 1997).…”
Section: Effects Of Ischemia and 1-hour Recirculation On Astrocytic Osupporting
confidence: 85%
“…As expected from previous studies of the metabolism of 1-14 C-acetate (Berl and Frigyesi, 1969;Haberg et al, 2001;Hassel et al, 1995), 14 C-radiolabel was also incorporated into glutamate, but at a lower specific activity than glutamine. The initial production of 14 C-glutamate from 14 C-acetate is also predominantly astrocytic based on the substantial impairment produced by the selective glial aconitase inhibitor, fluorocitrate (Fonnum et al, 1997).…”
Section: Effects Of Ischemia and 1-hour Recirculation On Astrocytic Osupporting
confidence: 85%
“…bolus injection of glucose, the concentration of glucose in the brain was not affected. 22 Thus, 13 C labeling in metabolites reported here reflects 13 C enrichment in brain and not blood glucose. In the present study, we found a decreased glutamate level in hippocampus whereas in cortex, glucose utilization and turnover of glutamate, glutamine, and GABA were increased.…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, NAA can supply both acetate and oxaloacetate to the TCA cycle for energy production (Nadler and Cooper, 1972a), at least in oligodendrocytes where ASPA is present. Glial cells preferentially utilize acetate for energy production through the TCA cycle, as opposed to neurons (Bluml et al, 2002;Hassel et al, 1995;Muir et al, 1986) suggesting that oligodendrocytes could make substantial use of NAA-derived acetate for energy production when myelination is complete. It has also been proposed that NAA could act as a reservoir of glutamate in the brain, wherein NAA is converted to aspartate in oligodendrocytes, which could then be converted to glutamate through the TCA cycle with favorable energetics (Clark et al, 2006).…”
Section: Fate Of Naa In Oligodendrocytes After Postnatal Myelinationmentioning
confidence: 99%